Glypicans and Heparan Sulfate in Synaptic Development, Neural Plasticity, and Neurological Disorders - Kamimura, Keisuke; Maeda, Nobuaki (Frontiers in Neural Circuits, 2021)
Heparan sulfate proteoglycans (HSPGs) are components of the cell surface and extracellular matrix, which bear long polysaccharides called heparan sulfate (HS) attached to the core proteins. HSPGs interact with a variety of ligand proteins through the HS chains, and mutations in HSPG-related genes influence many biological processes and cause various diseases. In particular, recent findings from vertebrate and invertebrate studies have raised the importance of glycosylphosphatidylinositol-anchored HSPGs, glypicans, as central players in the development and functions of synapses. Glypicans are important components of the synapse-organizing protein complexes, and serve as ligands for LRRTMs, LAR family RPTPs and GPR158, regulating synapse formation. Many of these interactions are mediated by the HS chains of glypicans. Neurexins are also synthesized as HSPGs and bind to some ligands in common with glypicans through HS chains. Therefore, glypicans and neurexins may act competitively at the synapses. Furthermore, glypicans regulate the postsynaptic expression levels of ionotropic glutamate receptors, controlling the electrophysiological properties and non-canonical BMP signaling of synapses. Dysfunctions of glypicans lead to failures in neuronal network formation, malfunction of synapses and abnormal behaviors that are characteristic of neurodevelopmental disorders. Recent human genetics revealed that glypicans and HS are associated with autism spectrum disorder, neuroticism and schizophrenia. In this review, we introduce the studies showing the roles of glypicans and HS in synapse formation, neural plasticity and neurological disorders, especially focusing on the mouse and Drosophila as potential models for human diseases.